Certain convex harmonic functions. (19th February 2002) - Kim, Yong Chan; Jahangiri, Jay M.; Choi, Jae Ho
Abstract : We define and investigate a family of complex-valued harmonic convex univalent functions related to uniformly convex analytic functions. We obtain coefficient bounds, extreme points, distortion theorems, convolution and convex combinations for this family.